ENGINEERING ETHICS AT TECHNICAL UNIVERSITY - Alfred A. Dulzon; Ekaterina V. Galanina (Moscow Polytechnic University, 2016)
The article covers the issues concerning the formation of engineers' social and cultural competences at higher education institutions. The concept of science and engineering moral neutrality is receding into the past, engineering education standards undergo changes. Not only specific technical knowledge plays an important role in training an engineer, but also such knowledge and skills as creative, systematic and critical thinking, sticking to professional ethics, teamwork, social context of engineering, etc. Forming an engineer's social and cultural competences is a requirement of various international engineering training standards. We have shown the necessity of teaching engineering ethics at technical universities and have given corresponding recommendations, which can be used in Russian higher education institutions.